A simple and quick sensitivity analysis method for methane isotopologues detection with GOSAT-TANSO-FTS. Issue 2 (10th February 2021) - Malina, Edward; Muller, Jan-Peter; Walton, David
Abstract : Measurements of methane isotopologues can differentiate between different source types, be they biogenic (e.g. marsh lands) or abiogenic (e.g. industry). Global measurements of these isotopologues would greatly benefit the current disconnect between 'top-down' (knowledge from chemistry transport models and satellite measurements) and 'bottom-up' ( in situ measurement inventories) methane measurements. However, current measurements of these isotopologues are limited to a small number of in situ studies and airborne studies. In this paper we investigate the potential for detecting the second most common isotopologue of methane ( 13 CH4 ) from space using the Japanese Greenhouse Gases Observing Satellite applying a quick and simple residual radiance analysis technique. The method allows for a rapid analysis of spectral regions, and can be used to teach university students or advanced school students about radiative transfer analysis. Using this method we find limited sensitivity to 13 CH4, with detections limited to total column methane enhancements of >6%, assuming a desert surface albedo of >0.3.